2016
DOI: 10.1002/ajp.22614
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A and nutrients in milk from great apes throughout lactation

Abstract: Milk macronutrients from great apes differed throughout lactation. Milk macronutrients but not IgA from non-human great apes and humans were quite similar. Milk protein was greater in Gorilla compared with Orangutan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
2
5
1
Order By: Relevance
“…This indicates that the bacterial community was gradually turning over with time. Nutrient content is largely stable in mature milk intra‐individually (Garcia et al, ; Hinde et al, ; Power et al, ), and we found no association of nutrient content predicting changes in the microbiome over time. Instead these changes over time may reflect EMT moving different bacteria from the mother's gut to the mammary gland and/or changes in the infant oral microbiome over time (Dzidic et al, ) that changes which bacteria colonize milk through retrograde flow during suction (Ascinar et al, ; Biagi et al, ).…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…This indicates that the bacterial community was gradually turning over with time. Nutrient content is largely stable in mature milk intra‐individually (Garcia et al, ; Hinde et al, ; Power et al, ), and we found no association of nutrient content predicting changes in the microbiome over time. Instead these changes over time may reflect EMT moving different bacteria from the mother's gut to the mammary gland and/or changes in the infant oral microbiome over time (Dzidic et al, ) that changes which bacteria colonize milk through retrograde flow during suction (Ascinar et al, ; Biagi et al, ).…”
Section: Discussioncontrasting
confidence: 54%
“…Milk samples for nonhuman primates were collected either voluntarily or while under anesthesia. Samples were collected with approved protocols from NZP IACUC and Zoo Atlanta Scientific Review Committee for western lowland gorillas, Bornean orangutans ( Pongo pygmaeus ), and Sumatran orangutans (Garcia, Power, & Moyes, ; Power et al, ) and UCLA and UC Davis IACUCs for rhesus macaques ( Macaca mulatta ; Hinde, Power, & Oftedal, ). Bonobo ( Pan paniscus ), chimpanzee ( Pan troglodytes ), and owl monkey ( Aotus nancymaae ) samples were collected as part of standard management procedures in accordance with institutional guidelines for care and use of animals at their respective facilities (see Table ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The human neonate is born with an immature, adaptive immune system; it is protected by maternal Immunoglobulin G that crosses the placenta by an active transport system that results in fetal blood concentration of IgG being higher that maternal blood [43]. After birth, if breastfed, the human neonate receives large doses of secretory Immunoglobulin A (sIgA) via breast milk; human breast milk has concentrations of sIgA 20-30 times higher than in gorilla or orangutan milk [44]. But eventually, the neonatal adaptive immune system must produce its own antibodies.…”
Section: Evolution Public Health and The One Health Conceptmentioning
confidence: 99%